2019
DOI: 10.1021/acs.jnatprod.8b00893
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Activity of Compounds Isolated from Anarrhinum pedatum

Abstract: Ten new iridoid glycosides (1–10) and two new monoterpenoids (11 and 12), together with nine known compounds (13–21), were isolated from the n-butanol extract of the aerial parts of Anarrhinum pedatum. The structural characterization of all compounds was performed by spectroscopic analysis, including 1D and 2D NMR and HRESIMS experiments. The isolates were assayed for their antiangiogenic activity by two in vivo models, using zebrafish embryos and chicken chorioallantoic membranes (CAMs). The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These iridoid derivatives isolated from N. reticulata induced cytotoxic and anti-inflammatory activities on hepatocarcinoma cells and the macrophage cell line, respectively [43][44][45]. The iridoid glycosides isolated from other plant species were also found to have an anti-angiogenic property and can suppress tumour migration and invasion [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…These iridoid derivatives isolated from N. reticulata induced cytotoxic and anti-inflammatory activities on hepatocarcinoma cells and the macrophage cell line, respectively [43][44][45]. The iridoid glycosides isolated from other plant species were also found to have an anti-angiogenic property and can suppress tumour migration and invasion [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…It has been found that compared with human umbilical vein endothelial cell and chicken embryo allantoic membrane models, the zebrafish model is more simplistic and practical, making it suitable for the screening of active ingredients in traditional Chinese medicine that exhibit antiangiogenic properties. In addition, the angiogenesis process of zebrafish embryos is very similar to that of malignant tumors ( 14 , 15 ). Therefore, in this study, we established a transgenic zebrafish model, investigated and observed the blood vessels of transgenic zebrafish using fluorescent labeling, and counted the intersegmental vessels (ISVs) to explore the inhibitory effect of tryptanthrin on angiogenesis.…”
Section: Introductionmentioning
confidence: 95%
“…In this paper, the isolation of one new iridoid glucoside, 6βacetoxyipolamiide (1), and thirteen (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) known congeners from two Lamiaceae species, Stachys ocymastrum and Premna resinosa, leaf extracts is reported. The structural determination of the isolated compounds was performed by monoand bidimensional NMR spectroscopic analysis as well as MS experiments.…”
Section: Introductionmentioning
confidence: 99%